Nuclear Deterrence Policy in the Post-Cold War Period - Gorda Gibradze; Alika Guchua (International Society of Philosophy and Cosmology, 2023)
During the Cold War, there were two nuclear superpowers, the Soviet Union and the United States, who had their own allies. They divided the whole world into spheres of influence, and there was an indirect struggle for supremacy between them. Therefore, they started a nuclear race for supremacy. As a result of these policies, both superpowers have built up enormous stockpiles and capabilities of nuclear weapons. All this could destroy the earth several times. Like the nuclear weapons in their arsenal today. After the Cold War, a new geopolitical order was created in the world, dominated by the USA. However, this dominance did not last long, as new geopolitical players became active in the world in the form of Russia and China. They have their own geopolitical interests and a unique vision of the world. After the creation of nuclear weapons, nine nuclear states emerged in the world. As well as a number of states that want to possess nuclear weapons. Therefore, it is important to pursue a policy of nuclear deterrence to make the world safer. The presented article discusses the policy of nuclear deterrence and the existing difficulties in the post-Cold War period. The aim of the work is to discuss the nuclear deterrence policy and analyze the existing threats in the process of establishing a new world order.